Impact of one-stop clinic on the clearance of COVID-19 surgical backlog - AlShareef, Yasir; AlShammary, Sami A.; Abuzied, Yacoub; AlAsseri, Yahya; AlQumaizi, Khalid I. (International Journal of Health Sciences, 2022)
Objective: During the COVID-19 pandemic, there was a significant decrease in the number of operated elective cases due to the shutdown procedures. This situation created a substantial surgical backlog. Several visits are generally necessary before a surgical decision making and booking the surgery time. Improving patient access by creating “one-stop” clinics might help decrease the number of visits before the surgery. This study investigated the effect of one-stop clinic application as a new care model on COVID-19 surgical backlog clearance. Methods: We conducted a quasi-experimental, interrupted time-series, pretest-posttest study design in the northern areas of Saudi Arabia. The study outcomes were the number of surgeries and the time elapsed from the first seen day to the booked room day. Results: A total of 358 surgeries were included. Of them, 107 (29.9%) surgeries were performed before initiation of the one-stop clinic and 251 (70.1%) after initiation. The median (quartile Q1, Q3) time elapsed from the first seen day until the booked OR day post-one-stop clinic was 10 (6-17), which was significantly lower than pre-one-stop clinic 20 (11-33), P < 0.0001. Conclusion: One-stop clinics shortened the period between first visit and booking in the operating room. One-stop clinics may alleviate the surgical backlog resulting from the COVID-19 crisis.